Breaking new ground or breaking the rules: strategic reorientation in U.S. industrial policy. - Fong, Glenn R. (International Security)
The writer examines strategic reorientation in U.S. industrial policy. He presents nine case studies that involved advanced technology in which such policy is integral: the development of interactive computer graphics; the beginnings of the Internet; advanced digital signal processing technology; parallel computing and artificial intelligence; semiconductor manufacturing research and development; a program that pushes technology to shrink more transistors onto a chip; a program that promotes the commercialization of new technologies; the funding of supercomputer research and fiber-optic networks; and an initiative that supported flat panel electronic display technologies. He concludes that such programs are indicative of the increasing capability of the U.S. to undertake programs that are directly salient to economic competitiveness.